2014
DOI: 10.1186/1687-6180-2014-133
|View full text |Cite
|
Sign up to set email alerts
|

Joint mean angle of arrival, angular and Doppler spreads estimation in macrocell environments

Abstract: In this paper, we propose a new low-complexity joint estimator of the mean angle of arrival (AoA), the angular spread (AS), and the maximum Doppler spread (DS) for single-input multiple-output (SIMO) wireless channel configurations in a macrocell environment. The non-line-of-sight (NLOS) case is considered. The space-time correlation matrix is used to jointly estimate the three parameters. Closed-form expressions are developed for the desired parameters using the modules and the phases of the cross-correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The other characteristic of the channel that has been modeled is the probability density function of the AoA. In literature [24], the AoA has been variously modeled. Some popular representations include, Von Mises, Laplacian and even Gaussian distribution.…”
Section: Channel Modelingmentioning
confidence: 99%
“…The other characteristic of the channel that has been modeled is the probability density function of the AoA. In literature [24], the AoA has been variously modeled. Some popular representations include, Von Mises, Laplacian and even Gaussian distribution.…”
Section: Channel Modelingmentioning
confidence: 99%
“…We realize that the angle of arrival (AOA) estimation [10,11] is an interesting study that can be applied for localization. Recently, it has been shown that multipleinput multiple-output (MIMO) orthogonal frequency division multiplexing (OFDM) channel state information (CSI) may be used as the observation data for localization based on AOA [9].…”
Section: Introductionmentioning
confidence: 99%